On the economic determinants of oil production - Cologni, Alessandro; Manera, Matteo (Energy economics, 2014)
In this paper, decisions regarding production in oil exporting countries are studied by means of theoretical analysis and empirical investigation. In particular, we aim at describing the relationship between oil production levels and changes in the world oil demand and prices. Intertemporal production decisions by a representative oil producer are modeled by means of a partial equilibrium model. In this theoretical model, oil producers are subject to exogenous shocks in world oil consumption and prices. Oil companies can change output levels only by incurring a fixed cost. Results from the simulation of this model show a strong relationship between oil production and changes in world oil consumption. On the contrary, the effects of changes in real oil prices on oil production decisions seem to be much lower. Results from the simulation of the theoretical model are then empirically investigated using time-series econometric techniques. The empirical evidence supports the hypothesis that oil producing countries are characterized by different responses to changes in world oil demand and in real oil prices. For many countries, production rapidly adjusts to changes in consumption whereas responses of oil production to innovations in real oil prices are found to be not statistically significant. In addition, when non-linearities in the relationship between world oil demand, prices and output levels are allowed for, evidence of asymmetric effects of shocks to exogenous variables on output levels is found for some countries. •Causal relationship between economic variables and production levels of oil exporting countries.•Simulation of a partial equilibrium model. Relationship between exogenous economic shocks and oil output levels.•Econometric analyses of the relationship between world oil demand, international prices and production levels.•Time-series analyses suggest a statistically significant relationship between changes in world oildemand and output.•For some countries, evidence of asymmetric effects of shocks to exogenous variables on production levels is found.